Integrative Effects of Feeding Aspergillus awamori and fructooligosaccharide on Growth Performance and Digestibility in Broilers: Promotion Muscle Protein Metabolism. (5th May 2014) - Saleh, Ahmed A.; Amber, Khairy; El-Magd, Mohammed A.; Atta, Mostafa S.; Mohammed, Ahmed A.; Ragab, Mohamed M.; Abd El-Kader, Hanaa
Abstract : This study was conducted to show the effect of Aspergillus awamori (AA), fructooligosaccharide (FOS), and combined Aspergillus awamori and fructooligosaccharide (AA + FOS) on growth, digestibility, blood parameters, and expression of some growth-related genes. A total of 60 broiler chicks at the age of 15 d were divided into a control group (n = 15 ) and 3 treatment groups. The control group was fed a basal diet, and the treatment groups were fed basal diets supplemented with 0.05% AA, 0.05% FOS, and combined of 0.05% AA and 0.05% FOS. Results from measurement of growth performance and digestibility revealed a significant increase in the body weight gain with improved feed conversion rate in the experimental groups. Interestingly, dry matter digestibility (DMD) and crude protein utilization (CPU) were improved. In addition, plasma total cholesterol and low density lipoprotein-cholesterol (LDL-C) were decreased, while plasma high density lipoprotein-cholesterol (HDL-C) was increased by feeding AA, FOS, and AA + FOS. Expressions of growth hormone secretagogue receptor ( GHSR ), insulin-like growth factor 1 ( IGF-1 ), and insulin-like growth factor 1 receptor ( IGF1R ) were increased in experimental groups. In conclusion, the supplementation of either Aspergillus awamori or fructooligosaccharide or both improves digestibility and growth performance probably by promoting skeletal muscle protein metabolism.